2004
DOI: 10.1007/s00439-004-1185-8
|View full text |Cite
|
Sign up to set email alerts
|

The human T locus and spina bifida risk

Abstract: The transcription factor T is essential for mesoderm formation and axial development during embryogenesis. Embryonic genotype for a single-nucleotide polymorphism in intron 7 of T ( TIVS7 T/C) has been associated with the risk of spina bifida in some but not all studies. We developed a novel genotyping assay for the TIVS7 polymorphism using heteroduplex generator methodology. This assay was used to genotype spina bifida case-parent trios and the resulting data were analyzed using the transmission disequilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…46,47 In contrast, heterozygous brachyury loss in mice results in a short tail and notochordal abnormalities, and in humans, congenital vertebral malformations (hemi vertebra, vertebral bars, supernumerary vertebrae, butterfly and wedge shaped vertebrae), neural tube defects (spina bifida and anencephaly) and sacral agenesis are associated with genetic variations in brachyury, the functions of which are variable and not always clear. [48][49][50] The failure to detect mutations in any of the coding regions, splice junctions and promoter region of this gene in 23 chordomas and the failure to show amplification of brachyury in 36 of 39 chordomas imply that the expression of brachyury mRNA and protein is likely to be driven by events in upstream molecules. Furthermore, despite the minor allelic gain of brachyury in three cases, a finding which corresponds to the array comparative genomic hybridisation data published earlier, we consider that amplification of this gene is also unlikely to account for the driving force in the growth and development of this tumour in view of the low copy number of the gene in the small number of cases that was identified.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 In contrast, heterozygous brachyury loss in mice results in a short tail and notochordal abnormalities, and in humans, congenital vertebral malformations (hemi vertebra, vertebral bars, supernumerary vertebrae, butterfly and wedge shaped vertebrae), neural tube defects (spina bifida and anencephaly) and sacral agenesis are associated with genetic variations in brachyury, the functions of which are variable and not always clear. [48][49][50] The failure to detect mutations in any of the coding regions, splice junctions and promoter region of this gene in 23 chordomas and the failure to show amplification of brachyury in 36 of 39 chordomas imply that the expression of brachyury mRNA and protein is likely to be driven by events in upstream molecules. Furthermore, despite the minor allelic gain of brachyury in three cases, a finding which corresponds to the array comparative genomic hybridisation data published earlier, we consider that amplification of this gene is also unlikely to account for the driving force in the growth and development of this tumour in view of the low copy number of the gene in the small number of cases that was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Other gene pathways, such as those genes that affect metabolism in diabetes and obesity, those affected by known teratogenic agents, those active in embryonic development, and those involved in DNA repair are also being investigated. 18,20,22,37,41 Open spinal dysraphisms are associated with trisomies 13 and 18, and have been reported with trisomies 2, 9, 14, 15, 16, 20, and 21. Neural tube defects have also been associated with partial trisomy of individual chromosomes.…”
Section: Folic Acidmentioning
confidence: 94%
“…Meckel syndrome, Waardenburg syndrome, and genetic abnormalities associated with 13q deletion syndrome. 1,11,18,[20][21][22]41,42 PRENATAL TESTING AND DIAGNOSTIC IMAGING E levated serum ␣-fetoprotein (AFP) testing during pregnancy helps identify the presence of open spinal defects. The optimum time for screening is 16 weeks.…”
Section: Folic Acidmentioning
confidence: 99%
“…They observed a bias in transmission of the C allele from heterozygous parents to offspring with neural tube defects in Dutch and UK families. Jensen et al [25] found that heterozygous parents transmitted the C allele to their offspring with spina bifida significantly more frequently than expected under the assumption of Mendelian inheritance. Moreover, the analyses suggested that the C allele acts in a dominant fashion, such that individuals carrying 1 or more copies of this allele have a 1.6-fold increased risk of spina bifida compared with individuals with 0 copies.…”
Section: Relationship Of the T Gene To Human Diseasesmentioning
confidence: 97%